(untitled) (INTERNATIONAL JOURNAL OF CONSTRUCTION ENGINEERING (IJCE), 2024)
The building industry is increasingly embracing sustainable practices to minimise environmental effect and improve long-term sustainability. High-performance lightweight concrete (HPLC) offers advantages such as reduced material consumption, enhanced structural efficiency, and minimised environmental impact. This study examines the development and characterization of High-Performance Liquid Chromatography (HPLC) in response to the growing need for eco-friendly construction materials. This study utilises both empirical research and computational simulations to improve the mechanical properties and longevity of HPLC by optimising material compositions and blending techniques. Various lightweight aggregates, like as recycled materials and natural resources, are evaluated to determine their suitability in the manufacture of HPLC. Supplementary cementitious elements, including as fly ash, slag, and silica fume, are included to enhance the strength, durability, and environmental sustainability. The efficacy of produced HPLC blends is assessed using mechanical analysis, encompassing the quantification of compressive strength, flexural strength, and modulus of elasticity. Durability assessments, encompassing examinations for resistance to freeze-thaw cycles, sulphate attack, and carbonation, ensure the enduring structural integrity of materials under diverse environmental conditions. Furthermore, life cycle assessment (LCA) and cost analysis are performed to evaluate the environmental and economic feasibility of incorporating HPLC into sustainable construction projects. This study aims to improve sustainable building practices and encourage the extensive adoption of High-Performance Liquid Chromatography (HPLC) in the construction industry. It does so by evaluating the environmental benefits and economic viability of using HPLC. Our research seeks to utilise the advantages of HPLC as an efficient and environmentally-friendly alternative to conventional concrete. Our efforts will establish the foundation for a created environment that is long-lasting and environmentally sustainable.